Legal Analysis of Product Use with Brand Name Riding in Ternate City, Indonesia - Ibrahim, Mardia; Laode, Muhammad Taufik; Ikrima, Nur Aida; Budiono, Arief (Dinasti Research, 2025)
This paper is entitled “Legal Analysis of Product Use with Brand Name Riding in Ternate City”. The existence of a brand has a major impact on business competition as well as on improving economic standards. This research analyzes the use of products that piggyback on the names of well-known brands. This study uses socio-legal research which is a combination of two methods in the form of dogmatic legal research and empirical research. Results show that products that piggyback on well-known brand names is a manifestation of bad faith as well as damaging reputation and deceiving consumers. Several Indonesian regulations prohibit such actions. Although the ban on piracy, counterfeiting, and the commercialization of goods resulting from IPR violations, including trademark piggybacking, should serve as a deterrent against trademark infringement, issues like business actors' ignorance of the law and the imitation culture continue to impede effective law enforcement. The legal ramifications of trademark infringement by piggybacking on brand names then refer to different effects or outcomes that may occur as a result of breaking the law or committing illegal conduct.